Poland-Möbius syndrome and disruption spectrum affecting the face and extremities: a review paper and presentation of five cases - Kuklík, M (Acta chirurgiae plasticae, 2000)
The author summarizes hitherto assembled experience with the clinical and genetic characteristics of Poland's and Möbius syndrome. Five selected case-records with this disease and the sequence of the Poland-Möbius syndrome are presented. Another case-record is devoted to an allied syndrome, hypoglossia-hypodactyly, found in a spontaneously aborted fetus. For establishment of a more accurate symptomatology, an irreplaceable place is held by anthropometric examination; for objectifying the asymmetry of the chest the so-called cyrtogram, the chest circumference recorded by means of a wire, is valuable. From the aspect of genetic counseling, preconception care is always provided to mothers from families with reproductive intentions, as well as ultrasonographic examination of the fetus in areas of assumed acral symptomatology (signaling phenotype). In two families ultrasonography was used for prenatal diagnosis. Invasive prenatal diagnosis by amniocentesis was employed in a family with Möbius syndrome. In these families dermatoglyphs have certain common characteristics, such a tendency towards simple patterns. In the wider family of one of our patients we detected in a cousin Parkes-Weber-Klippel-Trenaunay's syndrome, which may indicate common vascular predisposing factors.
Keywords: dospělí; Child, Preschool; Adult; lidé; Polandův syndrom; Phenotype; dítě; Moebiův syndrom; předškolní dítě; fenotyp; Child; Humans; Male; Poland Syndrome; mužské pohlaví; Mobius Syndrome; ženské pohlaví; Female